Looking for the peptide 2.05‐helix: A solvent‐ and main‐chain length‐dependent conformational switch probed by electron transfer across cα, α‐diethylglycine homo‐oligomers1. Issue 1 (19th January 2013) - Lettieri, Raffaella; Bischetti, Martina; Gatto, Emanuela; Palleschi, Antonio; Ricci, Elisabetta; Formaggio, Fernando; Crisma, Marco; Toniolo, Claudio; Venanzi, Mariano; Maran, Flavio; Toniolo, Claudio
Abstract The elusive, multiple fully extended (2.05‐helix) peptide conformation was searched with a series of Cα, α‐diethylglycine homo‐oligomers (n = 1 to 5) functionalized by an electron transfer (ET) donor···acceptor (D···A) pair in acetonitrile and chloroform solutions. In the former solvent, all peptides investigated were shown to populate the 310‐helix conformation, whereas in chloroform the two shortest members of the series (n = 1 and n = 2) adopt predominantly the 2.05‐helix. Interestingly, for the longest components (n = 3 to n = 5) in this latter solvent, an equilibrium between the 2.05‐ and 310‐helices takes place, the latter conformation becoming progressively more populated as the peptide main‐chain length increases. Time‐resolved fluorescence (TRF) experiments and molecular mechanics (MM) calculations were used in a combined approach to analyze the ET efficiencies and to associate a specific conformer (from MM) to an experimentally determined ET rate constant (from TRF). Therefore, because of the high sensitivity of the ET process to the D···A distance, ET can be used as a kinetic spectroscopic ruler, allowing for the characterization of the transition from a pure 310‐helix conformation to a 2.05‐/310‐helix equilibrium for the longest Deg homo‐peptides of this series upon changing the solvent from acetonitrile to chloroform. To our knowledge, this is the first time that the electronic coupling factor β for ET across a peptide chain in the 2.05‐helix conformation is provided. © 2012 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 51–63, 2013.